The influence of celebrities on the conspicuous consumption of Saudi youth - Ghada A. R. Al-Turif; Hessa A. R. Al-Sanad (Innovative Marketing, 2023)
This study aims to assess the influence of celebrities on the conspicuous consumption of Saudi youth. A descriptive study using a social survey method with 309 randomly selected Saudi students was conducted. A questionnaire was used to gather data. The model included 36 questions. The study utilized the Likert scale, SPSS statistical software, mono-variation analysis, the least difference (LSD) test. The assessment of the sample demographic variables shows that the research population is diversified. The results showed that the most prominent areas of conspicuous consumption for youths were buying clothes, perfumes, cosmetics, and jewelry (the average was 2.70 out of 3). It was also concluded that the major way that celebrities use to present products to the audience is the indirect marketing method (the average was 2.87 out of 3). The main reasons behind youth following celebrities were the celebrity’s attractiveness and a large number of followers (the average was 2.89 out of 3). The manifestations of celebrities’ influence on youths were apparent in their conspicuous consumption as the youths were interested in being the first to buy the products announced by celebrities, which gave them a sense of distinction compared to their friends (the average was 2.89 out of 3). Unplanned purchases were the main difficulty that youth faced in regard to budget management (the average was 2.75 out of 3). The study recommends intensifying awareness of rationalizing consumption and eliminating the negative values of conspicuous consumption among Saudi youths. AcknowledgmentInternational Review Board (IRB) Statement: IRB Registration Number with KACST, KSA:H-01-R-059 Informed Consent Statement: Informed Consent was obtained from all subjects involved in the study.This research project was funded by the Deanship of Scientific Research, Princess Nourah bint Abdulrahman University, through the Program of Research project Funding After Publication, grant No (PRFA-P-42-6).